Compressive Sensing Based Underwater Communication System. (2016) - Joseph, Jinu; Devi, M. Rema; Kumar, N. Suresh
Abstract: Underwater acoustic communication is an important research area having significant industrial and marine applications. Ocean exploration and observation, command and control of Autonomous Underwater Vehicles, coastal surveillance etc. are a few among the many applications. Underwater acoustic channel is considered as one of the most difficult communication media used today. Limited low data rate due to the narrow bandwidth of the channel, extensive and time varying Inter Symbol Interference results from multipath propagation etc are the main obstacles in this area. This paper aims to develop an efficient and reliable underwater communication system that solves the above problems very much. The Compressed Sensing (CS) based underwater communication system uses Orthogonal Frequency Division Multiplexing (OFDM) as an alternative to single carrier broadband modulation to achieve high data rate transmission. Compressed Sensing is an attractive technique for transmission of signals at sub-Nyquist rate leading to faster acquisition and power conservation. The proposed system comprising OFDM and CS will be a viable solution for reducing signal degradation and achieving high data rate transmission over an underwater acoustic channel.